Rancang Bangun Generator Magnet Permanen 16 Kutub untuk Pembangkit Listrik Tenaga Angin - Normansyah Normansyah (Electrical Network Systems and Sources, 2022)
Electricity is one of the main needs at this time. It has become a reality in the daily life of modern society that has advances in information and technology. Energy is one of the main needs in human life. The use of fuel for conventional power plants in the long term will exhaust the diminishing sources of oil, gas and coal and can also cause environmental pollution. An environmentally friendly energy source is the use of renewable energy, one of which is wind energy. Wind energy will be used as an energy source to produce mechanical energy which is then converted into electrical energy. The use of wind energy is expected to reduce the use of PLN electricity. A generator is a machine that can convert motion energy (mechanical) into electrical energy. (electrical). In a wind power plant, the generator moves because of wind energy (potential) that enters the blades and produces kinetic energy, then the resulting kinetical energy rotates the rotor of the engine, this rotation is called mechanical energy, and then the engine converts the mechanical power into electrical energy. The design, design and manufacture of a permanent magnet generator with a power of 150 W is used for the purposes of generating electric energy from low-speed wind energy. The components used are: Magnetic field, 12 magnets with a size of 2×1 cm, 0.4 mm email wire, shaft, bearing, 12 Volt DC lamp for generator testing.